DEVELOPMENT OF PROBLEM-BASED LEARNING STUDENT WORKSHEETS ON STATISTICAL MATERIAL ON THE ABILITY TO UNDERSTAND MATHEMATICS CONCEPTS - Rahadi Bimansah; Dewi Rahimah; Edi Susanto (Universitas Wiralodra, 2025)
This study aims to produce Problem-Based Learning student worksheets (LKPD-PBL) on statistical material on the ability to understand mathematical concepts for class VIII SMPN 17 Bengkulu City, which are valid and practical. The urgency of this study is based on the importance of enhancing students' ability to understand mathematical concepts. Preliminary observations indicate that many students struggle to deeply comprehend statistical concepts due to conventional teaching methods. Therefore, an innovation in teaching materials is needed to help students develop their conceptual understanding through the Problem-Based Learning (PBL) approach. This study was a Design Research (DR) using type development studies, consisting of level preliminary and level prototyping with flow formative evaluation, self-evaluation, one-to-one, expert review, small group, and field test. The study instrument consists of a validity questionnaire, a practicality questionnaire, and interviews. The study results showed that the development of LKPD-PBL was: 1) valid based on the results of revisions through the expert review and one-to-one stages regarding aspects of material, construction, language, and readability; 2) practical based on the results of revisions through the small group stage regarding ease, clarity, and usefulness.